The research of expectations and perceptions of Individuals towards service quality that are coming to sports center continually - Adnan Ersoy; Sihmehmet Yıgıt (Türk Spor ve Egzersiz Dergisi)
The aim of the research is to explore the expectations and pleasure of members who are coming to sports center continually. The universe of the research and the samples of forming sport centers is made up by the total (n=259) of members who are coming to sports center continually in the city of Gaziantep. To research the views of people coming to sport center about the pleasure towards service quality, the scale developed by Lam, Zhang and Jensen (1),the validity and reliability studies are done by Gürbüz, Koçak and Lam (1) in Turkey SQAS (Service Quality Assessment Scale) the scale of service quality is used. The internal consistency of the scale is tested by Cronbach Alpha techniques. To define the differences between the groups, “independent sample t test” and “the analysis of one way variance” are used. The reliability coefficient of service quality is found above 0.90.  As a result of research; the expectations are higher than perceptions in the evaluation of expectations and perceptions of the individuals who are coming to sport centers regularly, the sports centers are not in the level of meeting the needs of member as service quality.